2021
DOI: 10.1007/s00449-021-02648-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved catalytic performance of carrier-free immobilized lipase by advanced cross-linked enzyme aggregates technology

Abstract: The cross-linked enzyme aggregates (CLEAs) are one of the technologies that quickly immobilize the enzyme without a carrier. This carrier-free immobilization method has the advantages of simple operation, high reusability and low cost. In this study, ionic liquid with amino group (1-aminopropyl-3methylimidazole bromide IL) was used as the novel functional surface molecule to modify industrialized lipase (Candida rugosa lipase, CRL). The enzymatic properties of the prepared CRL-FIL-CLEAs were investigated. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…As commented in the introduction, the most used carrier-free immobilization method is the preparation of CLEAs; a plethora of publications and reviews have described CLEAs with multiple enzymes [12,42,57,58,67]. This methodology involves the precipitation of the enzyme molecules (with or without other reagents) and the ulterior crosslinking using mainly (but sometimes not only) GA [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As commented in the introduction, the most used carrier-free immobilization method is the preparation of CLEAs; a plethora of publications and reviews have described CLEAs with multiple enzymes [12,42,57,58,67]. This methodology involves the precipitation of the enzyme molecules (with or without other reagents) and the ulterior crosslinking using mainly (but sometimes not only) GA [51].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the other latest examples of CLEAs with CRL found in the literature, our CLEA-LC seems to be advantageous; for instance, Jiaojiao et al [67] recently reported CRL-CLEAs using an expensive amine-containing ionic liquid (1-aminopropyl-3methylimidazole bromide, FIL) as the functional surface molecule with which to modify CRL. The activity of this CLEA was tested only with a chromogenic standard substrate without testing it on any racemic substrate to check its stereoselection capability.…”
Section: Thermal Stability Of Crl Clea-lcsmentioning
confidence: 96%
See 1 more Smart Citation
“…An advantage of this technique is its ability to make the enzyme more pH stable. JiaoJiao et al [178] showed that lipase from Candida rugosa could be immobilized by the CLEAs methodology and its behavior improved as the enzyme became more stable at a particular pH compared to the free enzyme.…”
Section: Enzyme Immobilizationmentioning
confidence: 99%